Challenges in Teaching Literature in an EFL Context (A Case Study of Indonesian Students) - Jaufillaili; Noviani, Via; Erawati, Turini (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2023)
The significance of literature in language learning has grown considerably. This is particularly true in the context of English as a Foreign Language (EFL), where it is recognized as a valuable tool for enhancing English skills. Nonetheless, the focus on teaching English literature for its intrinsic value rather than solely as a means for language acquisition is limited, especially in Indonesia. Therefore, the purpose of this study is to explore the teaching of English literature to EFL students in Indonesian high schools. Specifically, the study aims to investigate the criteria employed by English literature teachers in selecting literary works, identify challenges faced by teachers when instructing EFL students in English literature, and examine the strategies they employ to overcome these challenges. The research entails a case study involving a teacher instructing two distinct English lessons at a senior high school in Indonesia. The findings reveal the following: Firstly, the primary considerations for selecting literary texts include factors such as length, language complexity, canonical status, and the author's cultural background. Secondly, challenges encountered encompass reading habits, English proficiency, and the availability of resources. Consequently, this research underscores the potential for further exploration within the realm of teaching English literature to EFL students in Indonesia, with the pursuit of effective instructional models being a noteworthy avenue for future investigation.